Hydrogen Sulfide Gas Exposure Induces Necroptosis and Promotes Inflammation through the MAPK/NF-κB Pathway in Broiler Spleen - Chi, Qianru (Oxid Med Cell Longev, 2019)
Hydrogen sulfide (H(2)S) is one of the main pollutants in the atmosphere, which is a serious threat to human health. The decomposition of sulfur-containing organics in chicken houses could produce a large amount of H(2)S, thereby damaging poultry health. In this study, one-day-old broilers were selected and exposed to 4 or 20 ppm of H(2)S gas (0-3 weeks: 4 ± 0.5 ppm, 4-6 weeks: 20 ± 0.5 ppm). The spleen samples were collected immediately after the chickens were euthanized at 2, 4, and 6 weeks. The histopathological and ultrastructural observations showed obvious necrosis characteristics of H(2)S-exposed spleens. H(2)S exposure suppressed GSH, CAT, T-AOC, and SOD activities; increased NO, H(2)O(2), and MDA content and iNOS activity; and induced oxidative stress. ATPase activities and the expressions of energy metabolism-related genes were significantly decreased. Also, the expressions of related necroptosis (RIPK1, RIPK3, MLKL, TAK1, TAB2, and TAB3) were significantly increased, and the MAPK pathway was activated. Besides, H(2)S exposure activated the NF-κB classical pathway and induced TNF-α and IL-1β release. Taken together, we conclude that H(2)S exposure induces oxidative stress and energy metabolism dysfunction; evokes necroptosis; activates the MAPK pathway, eventually triggering the NF-κB pathway; and promotes inflammatory response in chicken spleens.